Personal Listening device (PLD) usage among University Students and their audiometric profile during the shift to online learning post COVID-19 - Ana’am Alkharabsheh; Sara Alshurafa; Sara Alhanbali; Soha Garadat (PLoS ONE, 2025)
As the online learning increases post COVID-19 and in corresponding to the rise in the personal listening devices use, the present study aims to describe personal listening device (PLD) usage and auditory profile among a nationally sample of university students in Jordan and examine audiometric outcomes among them. The relationship between the usage of personal listening devices and hearing acuity will be examined. The relation between hours of personal listening devices use, volume levels, and self-report measures will additionally be explored. A total of 65 students from the University of Jordan were recruited. A full audiological tests battery including; routine puretone audiometry, extended high-frequency audiometry, and distortion product otoacoustic emissions, was conducted. Also, students were asked to fill the Arabic version of Tinnitus Handicap Inventory (THI) questionnaire and Hyperacusis Questionnaire (HQ). The use of personal listening devices does not seem to be related to the hearing threshold in the standard frequency range of 0.25-8 kHz for the majority of participants in this study. Using high-frequency audiometry, current results indicated a significant association between the usage of personal listening device and hearing thresholds at 18 and 20 kHz. While the distortion product otoacoustic emissions results showed that the signal to noise ratio (SNR) was affected (SNR < 6 dB) in only 20% of the students. With online learning becoming widely accepted as a standard educational approach post COVID-19, there is an anticipated surge in the usage of personal listening devices. Understanding the potential impact of this transition on the auditory well-being of students is crucial for ensuring their overall health and academic success. The use of personal listening devices for online learning might introduce potential risks to hearing and could align with the unsafe listening practices observed among young adults.